The trust effect towards online seller in social commerce - Ramli, Ramona; Abu Bakar, Asmidar; Ismail, Roslan; Aziz, Norshakirah (2017)
Social Commerce has gained its popularity among the Social Networks Sites (SNSs) user as online shopping medium.The popularity has engaged small online businesses to use the SNSs as their business platforms.However, trust remains as the main issues in Social Commerce due to its unique features.This study presents a conceptual model to evaluate the trustworthiness of online sellers which may influence customers’ purchase intention.A pilot questionnaire was designed and distributed as the instrument.Data was collected and analyzed using SPSS to test on the item’s reliability.The finding shows that the instrument can be empirically tested for further research.